0582 Effects of non-melanoma skin cancer on sleep and quality of life among renal transplant recipients. (25th May 2022) - Xerfan, Ellen; Leandro, Gabriela; Pires, Gabriel; Andersen, Monica; Tufik, Sergio; Facina, Anamaria; Tomimori, Jane
Abstract: Introduction: Non-melanoma skin cancer (NMSC) is highly prevalent in renal transplant recipients (RTR), due to the immunosuppressive effects of anti-rejection therapy after transplantation. Sleep disturbances can impair the immune system and enhance the repercussions of oxidative stress, which may play an important role in the carcinogenesis pathways. This survey aimed to compare data on quality of life and sleep in RTR with and without NMSC in a dermatology service. Methods: The study comprised 126 individuals, distributed in the following groups: RTR with NMSC (n=42), RTR without NMSC (n=43) and healthy controls (n=41). Participants answered a set of questionnaires, including the WHOQOL-bref, Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), and the Berlin Respiratory Disorder questionnaire (BRD). Results: The proportion of men were significantly higher among RTR (p=0.034). No statistically significant differences were observed regarding age, body mass index (BMI) and socioeconomic class. Transplantation living donors were statistically more frequent among RTR with NMSC (67% against 37% in the RTR without NMSC group; p=0.005). Among patients of the RTR with NMSC group, 9% had only basal cell carcinoma, 42% had only squamous cell carcinoma and 49% had both types of NMSC. There were no statistically significant differences on the final scores of the sleep questionnaires, except in 3 domains of the PSQI: sleep quality (p<0.001), sleep latency (p=0.01) and daytime dysfunction (p=0.02). Worse sleep quality was seen in the RTR with NMSC and controls, while worse sleep latency and more daytime consequences were found in both RTR clusters. All groups were predominantly composed of subjects with morning-type chronotype, low sleep quality and increased daytime sleepiness. In the WHOQOL, the physical domain was significantly impaired in the RTR groups (p<0.001). Conclusion: Although all groups were mainly composed of individuals with excessive daytime sleepiness and low sleep quality, there were no differences regarding quality of life and sleep between RTR and controls. Further long-term examination of kidney transplant recipients and their sleep pattern are warranted, as poor sleep may have a link with immunosuppression and organism imbalance, as well as on quality of life of these individuals. Support (If Any): AFIP, CAPES, CNPq, and FAPESP.